Paeoniflorin: a review of its pharmacology, pharmacokinetics and toxicity in diabetes - Ou, Xue; Yu, Zhijie; Pan, Chuanyu; Zheng, Xi; Li, Dandan; Qiao, Zhenzhen; Zheng, Xiaoyuan (Frontiers in Pharmacology, 2025)
The escalating global prevalence of diabetes underscores the urgency of addressing its treatment and associated complications. Paeoniflorin, a monoterpenoid glycoside compound, has garnered substantial attention in recent years owing to its potential therapeutic efficacy in diabetes management. Thus, this study aims to systematically overview the pharmacological effects, pharmacokinetics and toxicity of paeoniflorin in diabetes. Plenty of evidences have verified that paeoniflorin improves diabetes and its complication through reducing blood sugar, enhancing insulin sensitivity, regulating gut microbiota and autophagy, restoration of mitochondrial function, regulation of lipid metabolism, anti-inflammation, anti-oxidative stress, inhibition of apoptosis, immune regulation and so on. Paeoniflorin possess the characteristics of rapid absorption, wide distribution, rapid metabolism and renal excretion. Meanwhile, toxicity studies have suggested that paeoniflorin has low acute toxicity, minimal subacute and chronic toxicity, and no genotoxic or mutational toxic effects. In conclusion, this paper systematically elucidates the potential therapeutic application and safety profile of paeoniflorin in diabetes management.